PENGEMBANGAN SIKAP SPIRITUAL DAN SOSIAL DALAM PEMBELAJARAN PAI DI SMAN 9 REJANG LEBONG - Habib Ash.Sidiq; Nurmal, Ifnaldi; Idris, Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The research aims to analyze the development of spiritual attitudes carried out by Islamic Religious Education (PAI) teachers in SMAN 9 Rejang Lebong. The research methodology employs a qualitative approach, specifically field research, with data collection through observation, interviews, and documentation. Data analysis techniques include data reduction, data display, and data verification. Data validity is ensured through credibility (Internal Validity). The results of the research indicate that: 1) Development of Spiritual Attitudes by PAI Teachers in PAI Learning :Planning: PAI teachers set learning objectives related to the development of students' spiritual attitudes with religious values.Teachers utilize active learning, problem-based learning, multimedia presentations, and group discussions.Evaluation: Comprehensive evaluation is carried out through tests, student worksheets, self-assessment of spiritual attitudes, project assessment, and monitoring of student participation to measure conceptual understanding and development of spiritual attitudes. 2) Development of Social Attitudes by PAI Teachers :Planning: PAI learning planning for the development of social attitudes involves designing instructional strategies based on Islamic values such as honesty, discipline, and tolerance. Implementation: Learning activities involve direct interaction and application of religious concepts in daily life, focusing on cooperation and responsibility. Evaluation: Formative evaluation is conducted through observation of student participation and reflective tasks to monitor understanding and application of social Islamic values.